2005
DOI: 10.1002/cncr.21063
|View full text |Cite
|
Sign up to set email alerts
|

Validation of commonly used immunostains on cell-transferred cytologic specimens

Abstract: BACKGROUND.Immunocytochemical staining (ICC) is often limited by the lack of cell blocks that contain diagnostic cells or by the unavailability of smear materials.The cell-transfer technique, in which original smear material is divided into several pieces and then transferred to multiple slides, can facilitate multiple ICC on limited materials. However the reliability of the staining results has not been systematically evaluated. METHODS. RESULTS.One hundred pieces of transferred materials were immunostained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 9 publications
0
52
2
Order By: Relevance
“…1 Validation of CTT by Gong et al obtained adequate results in approximately 97% of cases. 2 Elsheikh and Corbin also validated the technique using touch imprints from fresh tumors and demonstrated a 100% concordance rate between cell-transferred pieces treated with antigen retrieval and the corresponding formalin-fixed tissue. 3 A similar correlation was performed at the study institution by Wu et al using cell-transferred cytologic smears and corresponding paraffin-embedded Figure 2.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…1 Validation of CTT by Gong et al obtained adequate results in approximately 97% of cases. 2 Elsheikh and Corbin also validated the technique using touch imprints from fresh tumors and demonstrated a 100% concordance rate between cell-transferred pieces treated with antigen retrieval and the corresponding formalin-fixed tissue. 3 A similar correlation was performed at the study institution by Wu et al using cell-transferred cytologic smears and corresponding paraffin-embedded Figure 2.…”
Section: Discussionmentioning
confidence: 87%
“…One important limitation to the use of CTT is that only ethanol-fixed direct smears can be used because air-dried methanol-fixed slides have previously been shown to have a false-negative rate of approximately 30% and also often demonstrate nonspecific background staining. 2 Another disadvantage of CTT is that the procedure is manual, requiring 5 to 7 hours to complete, which usually results in an additional day of turnaround time for the case. Overall, the benefits of CTT translate into a reduced need for repeat FNAs or core needle biopsies and an associated reduction in potential patient morbidity, as well as reduced health care costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weintraub et al (1990) reported a successful ICC study using three antibodies (AE1/AE3, CAM5.2, and leukocyte common antigen) on one single smear, an approach restricted by the number of antibodies one can apply and distinguish on a single slide. The "cell transfer" technique provides another approach to performing multiple ICC tests on limited smears (Brown and Tao 1992;Dabbs and Wang 1998;Gong et al 2005;Miller and Kubier 2002;Sherman et al 1994). Because of the impressive results achieved by this approach, Miller and Kubier (2002) advocated the routine use of "non-adhesive" slides to facilitate use of the cell transfer technique when necessary.…”
Section: Extending the Use Of Cell Samples By Technical Development: mentioning
confidence: 99%
“…This useful technique was originally validated for immunostains by Gong et al [9] in 2005, with a schematic illustration of the major steps of the cell transfer technique. Some modifications were made for molecular testing in our lab.…”
Section: Methodsmentioning
confidence: 99%